Education Based on the Qadiriyah Wa Naqsyabandiyah Order - Badrudin, Badrudin; Bahri Fauzin, Febri (Annpublisher, 2024)
The Qadiriyah wa Naqsyabandiyah order first entered Indonesia in the mid-19th century, brought by Ahmad Khatib ibn Abd al-Ghaffar al-Sambas al-Jawi and had a positive impact on society as far away as Banten. This research aims to explore congregation-based education in Banten. This research uses a qualitative approach with two methods, namely library research and field research, using observation and interview techniques conducted with figures there. This research shows that tarekat-based education uses the wiridan method to bring students closer to Allah. Apart from that, Erekat-based education is egalitarian, without discrimination towards society for anyone who wants to learn and know God. There is a need to develop tarekat-based education to be applied in other educational institutions.